On Collaborative Translation and Subjectivity in the Humanities. A Conversation with The Henri Meschonnic Reader’s Translator Team - Thiérard, Hélène (TTR)

(untitled) (Association canadienne de traductologie, 2024)
The publication of The Henri Meschonnic Reader finally offers English-speaking readers the opportunity to engage with Henri Meschonnic’s theoretical work in a coherent way. To realize this project, a team of six translator-scholars from the fields of linguistics, poetics, literary and translation studies worked together. The interview follows the Meschonnician idea that translating is an activity that transforms the translator’s subjectivity and examines its implications in the context of collaborative translation and (re)translation in the humanities. Looking back on their experience of working together, the translators reflect on how putting into practice the ethics of translation, defined by Meschonnic as “translating what the text does rather than what it says,” involves a conception of language as an activity, thereby challenging our understanding of the humanities and our systems of knowledge.